Building capacity for mainstreaming nature-based solutions into environmental policy and landscape planning - Mario V Balzan; Judita Tomaskinova; Marcus Collier; Lynn Dicks; Davide Geneletti; Miriam Grace; Davide Longato; Renata Sadula; Pavel Stoev; Anna Sapundzhieva (Research Ideas and Outcomes, 2020)
Nature-based solutions (NBS) is a term often used to refer to adequate green infrastructure that provides multiple benefits to society whilst addressing societal challenges. They are defined as actions to protect, sustainably manage and restore natural or modified ecosystems that address societal challenges effectively and adaptively, simultaneously providing human well-being and biodiversity benefits. Malta, the smallest member state of the EU, has been characterised by rapid economic growth and urbanisation and Maltese citizens had the highest rate of exposure to pollution, grime or other environmental problems, in the EU. The project ReNature aims to establish and implement a nature-based solutions research strategy for Malta with a vision to promote research and innovation and develop sustainable solutions whilst improving human well-being and tackling environmental challenges. Here, we introduce the opening of ReNature collection of research articles in the Open Access Research Ideas and Outcomes (RIO) journal to publish unconventional research outputs and training materials. It will host key outputs relating to the sustainable use of biodiversity, biodiversity – ecosystem functioning, green infrastructure and ecosystem service assessments across rural-urban gradients, equitable access to the benefits derived from nature in cities and socio-environmental justice, payments for ecosystem services, and designing nature-based solutions.